INTEGRAZIONE FRA ARCGIS E EPANET2 PER LA MODELLAZIONE IDRAULICA DELLE RETI - Scandura, Mario (GEOmedia, 2015)
Reached the knowledge of networks and consumption, both geolocated, the need has arisen to verify, through simulations, the behavior and efficiency of the water distribution system. The idea was to integrate the SIT, platform ArcGIS 10.1, the modeling software EPANET2. By analyzing the needs of Epanet you modified the data model of pipelines and equipment, in order to make them compatible, and have addressed the main problems arising from these analyzes. The identification and corroboration of delivery nodes to determine the value of the application of the network, and the management of valves and gate valves in the SIT that are represented as point features, while in Epanet are treated as strings. For the determination of the application, the absence of data of the capillaries, it is proceeded in an empirical creating polygons of Thyessen related to the nodes dispensing, and "capturing" the counters pertaining to each polygon and then summing the relative consumptions, taken by the management system . For valves it is made of a procedure in the import software in Epanet that turns the nodes into arcs, and in the export of SIT return to the pressure values upstream and downstream populate various fields of the table on time of the valves.